Beer's History of British Socialism - Feis, Herbert; Beer, M. (Quarterly Journal of Economics, 1921)
Journal Article Beer's History of British Socialism Get access Herbert Feis Herbert Feis Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 35, Issue 4, August 1921, Pages 596–602, https://doi.org/10.2307/1882427 Published: 01 August 1921